High School Students' Epistemic Cognition and Argumentation Practices during Small-Group Quality Talk Discussions in Science - Liwei Wei; Carla M. Firetto; Rebekah F. Duke; Jeffrey A. Greene; P. Karen Murphy (MDPI AG, 2021)
For high school students to develop scientific understanding and reasoning, it is essential that they engage in epistemic cognition and scientific argumentation. In the current study, we used the AIR model (i.e., Aims and values, epistemic Ideals, and Reliable processes) to examine high school students' epistemic cognition and argumentation as evidenced in collaborative discourse in a science classroom. Specifically, we employed a qualitative case study approach to focus on four small-group discussions about scientific phenomena during the Quality Talk Science intervention (QTS), where students regularly received explicit instruction on asking authentic questions and engaging in argumentation. In total, five categories of epistemic ideals and five categories of reliable processes were identified. Students demonstrated more instances of normative epistemic ideals and argumentative responses in the discussions after they received a revised scientific model for discussion and explicit instruction on argumentation. Concomitantly, there were fewer instances of students making decisions based on process of elimination to determine a correct scientific claim. With respect to the relationship of epistemic cognition to authentic questioning and argumentation, the use of epistemic ideals seemed to be associated with the initiation of authentic questions and students' argumentation appeared to involve the use of epistemic ideals.